Self-Esteem pada Emerging Adulthood Pengguna Instagram: Ditinjau Dari Pola Asuh Orang Tua - Nadya Kamila; Puspa Rahayu Utami Rahman; Dinda Aisha (EduInovasi: Journal of Basic Educational Studies, 2025)
Instagram users entering emerging adulthood are vulnerable to self-assessment, which can increase self-acceptance, while negative comments can cause feelings of rejection. This condition is related to self-esteem, which is influenced by parenting patterns, among other factors. This study aims to determine the effect of parenting patterns on self-esteem in emerging adulthood among Instagram users in Bekasi. This study uses a quantitative method with a causality design and purposive sampling technique. Since the population size is unknown, the sample size was determined using Cochran's formula, resulting in 204 respondents aged 18–25 years. The research instruments included the Rosenberg Self-Esteem Scale (RSES) and the Parental Authority Questionnaire (PAQ) versions for fathers and mothers. The results showed that, partially, authoritarian fathering and authoritative mothering significantly influenced self-esteem, while permissive fathering, permissive mothering, authoritarian mothering, and authoritative fathering did not. Simultaneously, authoritarian fathering and authoritative mothering influenced self-esteem with an effect size of 10.3%.